Membangun Karakter Bangsa : Integrasi Nilai-Nilai Pancasila melalui Pembelajaran PBL di Kelas V SDN Kertobanyon - Zahra Khusnati; Nurul Kusuma Dewi; Tri Susi Artina Wati (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The purpose of this study was to use the Problem-Based Learning (PBL) paradigm to improve the understanding and application of Pancasila values in fifth grade students of Kertobanyon Elementary School. Classroom Action Research (CAR) was the methodology used; this study was conducted in two cycles, each consisting of planning, action implementation, observation, and reflection. Observation data from the first cycle showed that students' understanding of Pancasila values was still limited to theoretical knowledge and involvement in group discussions was still low. After adjustments were made in the second cycle, such as a more in-depth explanation of PBL and stronger motivation, student participation increased significantly. They became more active in discussions, expressed opinions, and worked together with group members to solve problems. In addition, students' understanding of Pancasila values also developed, and they were able to recognize and use these principles in authentic situations. Students' ability to collaborate and think critically was positively impacted by the use of the PBL model. Overall, this study shows that the PBL paradigm has succeeded in improving the standard of teaching of Pancasila Education while also fostering students' capacity to think critically and work together in teams. Therefore, the PBL model is worthy of evaluation as a teaching strategy that can be used more widely to instill Pancasila values in elementary schools.